Pollution In The Lagoons of Central-West Jeddah City - Alghamdi, Sara Husain; Almalki, Abrar Abdulhadi (Journal of natural sciences, life and applied sciences, 2025)
Water quality is one of the most important environmental factors affecting human health and the sustainability of ecosystems, as it reflects the levels of pollution and the extent to which water resources are influenced by various human activities. This study aims to determine the variation in pollution among three lagoons located in the western part of Jeddah city. The study relies on remote sensing techniques and geographic information systems to analyze the spatial distribution of environmental indicators.The research is based on the descriptive-analytical method to describe the study area, analyze the spatial distribution of pollutants using Sentinel-2 satellite data, and extract the following spectral indicators: (NDCI - NDTI - TSS) through the Google Earth Engine platform.The results revealed that Al-Arbaeen lagoon recorded the highest average concentration of total suspended solids (TSS) with a mean of 2856 mg/L, followed by Al-Shabab lagoon with an average of 1756 mg/L, while Al-Salam lagoon was the least polluted with an average of 698 mg/L. The spatial variation among the lakes reached 167%, reflecting differences in pollution intensity. The study recommends continuous environmental monitoring using remote sensing technologies and ongoing water analysis studies to identify any potential changes that may occur.
Keywords: lagoon; pollution; Environmental Geography; Remote Sensing